Pembuatan Briket Dari Kulit Kacang Tanah Dan Kulit Kopi Dengan Getah Damar Sebagai Perekat - Manalu, Bonita Restana; Irianty, Rozanna Sri; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bio-charcoal briquettes are one of the ingredients of fuel that derived from biomass. Biomass is one of the sources of energy that can be replaces. One of biomass that is used in this research is coffee skin and peanut skin. The research is aimed to utilize waste biomass as material fuel alternatives and determine the best comparison of coffee skin and peanut skin. This research is carried out a comparison between coffee skin and peanut skin with a ratio is 1:1, 1:2, 1:3, 2:1 and 3:1 with the amount of damar resin 20% w/w. tests were carried out the water content, ash content, volatile matter, heat value, and rate of combustion. The result of the analysis are obtained: the lowest water content for the ratio 3:1 at 12.85%, the lowest ash content at the ratio 2:1 at 7.07%, the lowest volatile matter for the ratio 1:3 at 48.26%, the highest heating value for the ratio 3:1 at 7151.32 cal/g and the best rate of combustion for the ratio 1:1 at 0.1716 g/min. Keywords: Briquette Charcoal, Coffee Skin, Damar, Peanut Skin